Experimental and theoretical investigation of fuel reforming for fuel cell applications - Wang, Hongmin (2008)
The autothermal reforming system developed in this study was proved to be feasible for hydrogen generation using natural gas and methanol as the feedback. In this research project, a good balance between numerical simulation and experimental investigation was carried out. A simulation program for thermodynamic analysis of the autothermal fuel reforming process was developed.